EVALUATION OF PERSONNEL MANAGEMENT AT SDN JREBENG KIDUL PROBOLINGGO CITY AND SDN KARENG KIDUL PROBOLINGGO REGENCY - Prastiwi Sriwijayanti, Ribut (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2021)
Abstract: The general purpose of this study was to review personnel management at SDN Jrebeng Kidul Kota Probolinggo and SDN Kareng Kidul probolinggo. More specifically, the purpose of this research is to describe the components of personnel management, namely recruitment, selection, development, maintenance and empowerment of personnel. This research design is a qualitative approach with this type of evaluation. The research design used is to capture results in the field by means of data collection, compare the results of data collection obtained by standards, provide proposals to improve, improve focus that is not in accordance with the theory, and create an evaluation matrix. One principal from SDN Jrebeng Kidul, one principal from SDN Kareng Kidul, 5 teachers for SDN Jrebeng Kidul and 6 teachers for SDN Kareng Kidul were the subjects of this research. The method of data collection is carried out with in-depth interviews, participating observations, and document studies. Analysis of personnel management work, human resources plan in privately paid teacher recruitment and recruitment process has been good but needs to be improved. Personnel management selection process needs to use multi method of selection. Assessment of work performance, counseling, discipline, training and development of personnel management need to be continuously developed by the leadership of the institution. The maintenance components that need to be improved are compensation, employee relations, employee service, and safety and health. Personnel audits, job satisfaction and career security and health plan also need to be optimized on the usage component. Evaluation of personnel management does need to be continuously optimized regularly and periodically. Keywords: English translation. evaluation; personnel management components; primary school. Abstrak: Tujuan umum penelitian ini adalah mengkaji manajemen personalia di SDN Jrebeng Kidul Kota Probolinggo dan SDN Kareng Kidul Kabupaten Probolinggo. Lebih spesifik, tujuan riset ini adalah mendeskripsikan komponen-komponen manajemen personalia yaitu rekrutmen, seleksi, pengembangan, pemeliharaan dan pemberdayaan personalia. Rancangan riset ini adalah pendekatan kualitatif dengan jenis evaluasi. Desain riset yang digunakan adalah memotret hasil di lapangan dengan cara pengumpulan data, membandingakn hasil pengumpulan data yang diperoleh dengan standar, memberikan usulan guna memperbaiki, menyempurnakan fokus yang belum sesuai dengan teori, dan membuat matriks evaluasi. Satu kepala sekolah dari masing-masing institusi dan 5 guru untuk SDN Jrebeng Kidul dan 6 Guru untuk SDN Kareng Kidul, dijadikan subjek riset ini. Metode pengumpulan data dilakukan dengan wawancara mendalam, pengamatan berperan serta, studi dokumen. Analisa pekerjaan manajemen personalia, perencaan SDM dalam rekrutmen guru privately paid dan proses rekrutmen sudah baik tetapi perlu ditingkatkan. Proses seleksi manajemen personalia perlu menggunakan penggunaan multi metode seleksi. Penilaian prestasi kerja, konseling, disiplin, latihan dan pengembangan manajemen personalia perlu terus dikembangkan oleh pimpinan lembaga. Komponen pemeliharaan yang perlu ditingkatkan adalah pemberian kompensasi, hubungan baik karyawan, pelayanan karyawan, dan keamanan serta kesehatan. Audit personalia, kepuasan kerja dan perencaanan karier keamanan dan kesehatan juga perlu dioptimalkan pada komponen penggunaan. Evaluasi manajemen personalia memang perlu terus dioptimalkan secara rutin dan berkala. Kata kunci: evaluasi; komponen manajemen personalia; sekolah dasar.